The Complete Chloroplast Genome of Chinese Bayberry (Morella rubra, Myricaceae): Implications for Understanding the Evolution of Fagales - Liu, Lu-Xian; Li, Rui; Worth, James R. P.; Li, Xian; Li, Pan; Cameron, Kenneth M.; Fu, Cheng-Xin (Frontiers in Plant Science, 2017)
Morella rubra (Myricaceae), also known as Chinese bayberry, is an economically important, subtropical, evergreen fruit tree. The phylogenetic placement of Myricaceae within Fagales and the origin of Chinese bayberry’s domestication are still unresolved. In this study, we report the chloroplast (cp) genome of M. rubra and take advantage of several previously reported chloroplast genomes from related taxa to examine patterns of evolution in Fagales. The cp genomes of three M. rubra individuals were 159,478 bp, 159,568 bp and 159.586 bp in length, respectively, comprising a pair of inverted repeat (IR) regions (26,014–26,069 bp) separated by a large single-copy (LSC) region (88,683–88,809 bp) and a small single-copy (SSC) region (18,676–18,767 bp). Each cp genome encodes the same 111 unique genes, consisting of 77 different protein-coding genes, 30 transfer RNA genes and four ribosomal RNA genes, with 18 duplicated in the inverted repeats. Comparative analysis of chloroplast genomes from four representative Fagales families revealed the loss of infA and the pseudogenization of ycf15 in all analyzed species, and rpl22 has been pseudogenized in M. rubra and Castanea mollissima, but not in Juglans regia or Ostrya rehderiana. The genome size variations are detected mainly due to the length of intergenic spacers rather than gene loss, gene pseudogenization, IR expansion or contraction. The phylogenetic relationships yielded by the complete genome sequences strongly support the placement of Myricaceae as sister to Juglandaceae. Furthermore, seven cpDNA markers (trnH-psbA, psbA-trnK, rps2-rpoC2, ycf4-cemA, petD-rpoA, ndhE-ndhG and ndhA intron) with relatively high levels of variation and variable cpSSR loci were identified within M. rubra, which will be useful in future researches characterizing the population genetics of M. rubra and investigating the origin of domesticated Chinese bayberry.